Implementasi Pendidikan Karakter Berbasis Imtaq di SMP A. Wahid Hasyim Tebuireng Jombang - Kurroti A'yun; Siti Khomariyah; Khudriyah Khudriyah (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2019)
The future challenge in education is creating individuals who are able to learn for life. The challenge of shifting values ??in society will bring a value crisis. To avoid it is implementing of character education to improve the quality of faith and piety. This study aims to describe the implementation of character education. This research is a qualitative research. Using interview, observation, and documentation as techniques of collecting data, then the data was analyzed by Miles and Huberman models. The research results showed that the implementation of character education through: habitual worship before school, in the class, rest, and before going home; giving advice inside and outside the learning process; exemplary teacher in starting the application of character education; internalization by focusing on cognition dimension and value, as well as extracurricular and religious programs. The character values ??applied are: sincerity, honesty, responsibility, hard work, and tasammuh.